2022
DOI: 10.1001/jamapediatrics.2022.3940
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depressive Symptoms and Disorders in Children and Adolescents With Migraine

Abstract: ImportanceThough it is presumed that children and adolescents with migraine are at risk of internalizing symptoms and disorders, high-level summative evidence to support this clinical belief is lacking.ObjectiveTo determine if there is an association between internalizing symptoms and disorders and migraine in children and adolescents.Data SourcesA librarian-led, peer-reviewed search was performed using MEDLINE, Embase, PsycINFO, and CINAHL databases (inception to March 28, 2022).Study SelectionCase-control, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 96 publications
0
48
0
1
Order By: Relevance
“…Mechanism by which this therapy works in not fully understood but believed to be related to its ability to decrease intracranial pressure. Other small case series have shown some benefit with agents such as topiramate, methysergide, propranolol, naproxen and IV metoclopramide (1). Our patient's headache meets the diagnostic criteria for primary cough headache and has shown marked improvement in both frequency and intensity of headaches following onabotulinum toxin therapy.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Mechanism by which this therapy works in not fully understood but believed to be related to its ability to decrease intracranial pressure. Other small case series have shown some benefit with agents such as topiramate, methysergide, propranolol, naproxen and IV metoclopramide (1). Our patient's headache meets the diagnostic criteria for primary cough headache and has shown marked improvement in both frequency and intensity of headaches following onabotulinum toxin therapy.…”
Section: Discussionmentioning
confidence: 56%
“…The International Headache Society defines primary cough headache as a headache, precipitated by coughing or straining in the absence of any intracranial disorder lasting up to 30 minutes (1). The etiology of primary cough headaches is believed to be related to elevated intracranial pressure which results from the increased central venous pressure that occurs with coughing (1,3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent meta-analyses of published studies, children and adolescents with migraine were shown to be more likely to have anxiety symptoms and disorders as well as depressive symptoms and disorders than healthy children and adolescents. Interestingly, the same results were seen in clinical and community/population-based samples, and there was no evidence of publication bias [ 41 ].…”
Section: Predictors Of Psychological Comorbidities Of Headache In Chi...mentioning
confidence: 59%